Antiphospholipid syndrome (APS) in patients with systemic lupus erythematosus (SLE) implies a more severe disease with more damage accrual and higher mortality. (October 2020) - Riancho-Zarrabeitia, Leyre; Martínez-Taboada, Victor; Rúa-Figueroa, Iñigo; Alonso, Fernando; Galindo-Izquierdo, María; Ovalles, Juan; Olivé-Marqués, Alejandro; Fernández-Nebro, Antonio; Calvo-Alén, Jaime; Menor-Almagro, Raúl; Tomero-Muriel, Eva; Uriarte-Isacelaya, Esther; et al.
Introduction: Antiphospholipid antibodies (aPL) have been associated with organ damage and certain features in systemic lupus erythematosus(SLE) patients. Our aim was to investigate the differences between SLE patients according to the presence of aPL and/or clinical antiphospholipid syndrome (APS). Materials and methods: Patients from the RELESSER-T registry were included. RELESSER-T is a Spanish multicenter, hospital-based, retrospective, SLE registry. Results: We included 2398 SLE patients, 1372 of whom were positive for aPL. Overall 1026 patients were classified as SLE, 555 as SLE-APS and817 as SLE-aPL. Regarding cardiovascular risk factors, SLE-APS patients had higher rates of hypertension, dyslipidemia and diabetes than those with SLE-aPL and SLE ( p < 0.001). SLE-APS patients showed higher rates of neuropsychiatric, cardiac, pulmonary, renal and ophthalmological manifestations than the other groups ( p < 0.001). SLE-APS patients presented greater damage accrual with higher SLICC values (1.9 ± 2.2 in SLE-APS, 0.9 ± 1.4 in SLE-aPL and 1.1 ± 1.6 in SLE, p < 0.001) and more severe disease as defined by the Katz index (3 ± 1.8 in SLE-APS, 2.7 ± 1.7 in SLE-aPL and 2.6 ± 1.6 in SLE, p < 0.001). SLE-APS patients showed higher mortality rates ( p < 0.001). Conclusions: SLE-APS patients exhibited more severe clinical profiles with higher frequencies of major organ involvement, greater damage accrual and higher mortality than SLE-aPL and SLE patients.